PHARMACEUTICAL COMPOUND REMOVAL DURING MIXED LIQUOR FILTRATION IN MEMBRANE BIOREACTOR OPERATED UNDER LONG SLUDGE AGE (Jurnal Teknologi (Sciences & Engineering), 2018)
Removals of 10 pharmaceutical compounds by different size particle fractions in the mixed liquor of a membrane bioreactor (MBR) operated under infinite solid retention time (SRT) were investigated. The distribution of pharmaceutical compounds of different particle size fraction in the mixed liquor of MBRs sludge was determined by fractionating the particles into different size fractions by using different separation techniques. Permeate obtained from each membrane filter was analyzed for residual concentration of pharmaceut8cal compounds using LC-MS/MS and HPLC-UV/Vis analyses. High removals (>80%) of DCF, TMP, NPX, IBP and TCS were observed but CBZ removals were low (<40%). Adsorption onto coarse particle (>0.45 Âµm) was the major phenomena responsible for the removal of hydrophobic compounds while adsorption onto fine particles and gel-like substances (1 kDa-0.45 Âµm) contributed significantly to the removals of hydrophilic and moderate hydrophobic compounds. The Majority of pharmaceutical compounds except CBZ and SMX could be adsorbed onto fine particles and gel-like substances and subsequently rejected during membrane filtration in the MBR. Operation of the MBR at high sludge concentration under long sludge age condition helped enhancing the removals of several pharmaceutical compounds via adsorption onto coarse and fine particles.